Wnt-5A augments repopulating capacity and primitive hematopoietic development of human blood stem cells in vivo - Murdoch, Barbara (The National Academy of Sciences, 2003)
Human hematopoietic stem cells are defined by their ability to repopulate multiple hematopoietic lineages in the bone marrow of transplanted recipients and therefore are functionally distinct from hematopoietic progenitors detected in vitro. Although factors capable of regulating progenitors are well established, in vivo regulators of hematopoietic repopulating function are unknown. By using a member of the vertebrate Wnt family, Wnt-5A, the proliferation and differentiation of progenitors cocultured on stromal cells transduced with Wnt-5A or treated with Wnt-5A conditioned medium (CM) was unaffected. However, i.p. injection of Wnt-5A CM into mice engrafted with human repopulating cells increased multilineage reconstitution by >3-fold compared with controls. Furthermore, in vivo treatment of human repopulating cells with Wnt-5A CM produced a greater proportion of phenotypically primitive hematopoietic progeny that could be isolated and shown to possess enhanced progenitor function independent of continued Wnt-5A treatment. Our study demonstrates that Wnt-5A augments primitive hematopoietic development in vivo and represents an in vivo regulator of hematopoietic stem cell function in the human. Based on these findings, we suggest a potential role for activation of Wnt signaling in managing patients exhibiting poor hematopoietic recovery shortly after stem cell transplantation.